The role of renin-angiotensin-aldosterone system (RAAS) genes in the development of hypertrophy in hypertrophic cardiomyopathy (HCM) - Carstens, N. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2009.